Histidine-rich glycoprotein inhibits TNF-α–induced tube formation in human vascular endothelial cells - Hatipoglu, Omer Faruk; Nishinaka, Takashi; Yaykasli, Kursat Oguz; Mori, Shuji; Watanabe, Masahiro; Toyomura, Takao; Nishibori, Masahiro; Hirohata, Satoshi; Wake, Hidenori; Takahashi, Hideo (Frontiers in Pharmacology, 2025)
IntroductionTumor necrosis factor-α (TNF-α)-induced angiogenesis plays a critical role in tumor progression and metastasis, making it an important therapeutic target in cancer treatment. Suppressing angiogenesis can effectively limit tumor growth and metastasis. However, despite advancements in understanding angiogenic pathways, effective strategies to inhibit TNF-α-mediated angiogenesis remain limited.MethodsThis study investigates the antiangiogenic effects of histidine-rich glycoprotein (HRG), a multifunctional plasma protein with potent antiangiogenic properties, on TNF-α-stimulated human endothelial cells (EA.hy926). Tube formation assays were performed to assess angiogenesis, and gene/protein expression analyses were conducted to evaluate HRG’s effects on integrins αV and β8. The role of nuclear factor erythroid 2-related factor 2 (NRF2) in HRG-mediated antiangiogenic activity was also examined through nuclear translocation assays and NRF2 activation studies.ResultsAt physiological concentrations, HRG effectively suppressed TNF-α-induced tube formation in vitro and downregulated TNF-α-induced expression of integrins αV and β8 at both the mRNA and protein levels. HRG treatment promoted NRF2 nuclear translocation in a time-dependent manner. Furthermore, activation of NRF2 significantly reduced TNF-α-induced tube formation and integrin expression, suggesting that NRF2 plays a key role in HRG-mediated antiangiogenic effects.Discussion and ConclusionOur findings indicate that HRG suppresses TNF-α-induced angiogenesis by promoting NRF2 nuclear translocation and transcriptional activation, which in turn inhibits integrin αV and β8 expression. Given the essential role of angiogenesis in tumor progression, HRG’s ability to regulate this process presents a promising therapeutic strategy for cancer treatment.